Features and Factors Associated with Drinking Problems or Illegal Drugs Use: A Cross Sectional Cohort Study with Patients of a Psychosocial Care Service - Di Pietro, Giuliano; Melo Ribeiro da Silva, Ravena; Costa Santos, Jessyca; Santos Santana, Tenisson; A. de Menezes Rezende, Breno; Paula de Araujo Santana, Ana; Alves de Oliveira, Maraiza; Batista dos Santos, Camila; Secundo dos Santos, Jussara; Almeida Souza, Adriane; C. da Silva Santos, Jamille; da Costa Ribeiro Silva, Riviane; et al. (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2016)
Background: Abusive alcohol consumption is a public healthcare problem all across the world, carrying a heavy toll of almost 6% of all deaths. Nearly 5% of the world population makes use of illicit drugs frequently. The treatment for patients with any substance abuse disorder, whether it is alcohol or another drug, requires specialized view. The purpose of this research was to characterize a group of users at a Psychosocial Care Center for Alcohol and other Drugs, drawing a social demographic profile, consumption habits, assessing the connection of addiction history in the family and the problems resulting from the use. Methods: Three hundred patients are registered and attending the institution regularly in the Psychosocial Care Center for Alcohol and other Drugs, For statistical dates 276 patients completed all the steps of the research and these were used for the statistic demonstration. The study was conducted in a small town in the countryside of Brazil’s northeast were included in a cross sectional cohort study in which several social and demographic variables were analyzed: gender, age, ethnicity, educational background, occupational status, and others, regarding consumption habits and problems resulting from the use. The analysis was carried out using the Statistical Package for the Social Sciences SPSS 20.0, and significance (p ≤0.05) based on Pearson’s correlation test. Results: 94.6% of the individuals analyzed were male, 20% of them reportedly white and at an average age of 36, having started using drugs at the age of 18 or less. Alcohol and cannabis were the ones used at the earliest stages. Data showed multiple chemical dependency in 65.2% of patients, predominantly alcohol, cannabis, tobacco, cocaine and crack, of those, almost 85% were alcohol dependent. The study showed a reverse correlation owing to the fact that the variety of drugs used tend to decrease as individuals get older. Family relationships and work performance were shown to be the most affected by drug abuse. Conclusion: The individuals who seek help at the Psychosocial Care Center for Alcohol and other Drugs are almost exclusively male, employed, with an average 14-year-long history of substance abuse. Although multiple chemical dependencies are a relevant aspect, alcohol remains the predominant drug among users.
Keywords: Alcohol